1996
DOI: 10.1128/jb.178.14.4027-4030.1996
|View full text |Cite
|
Sign up to set email alerts
|

Alkylresorcinols are abundant lipid components in different strains of Azotobacter chroococcum and Pseudomonas spp

Abstract: The occurrence of various amounts of 5-n-alkylresorcinols was shown in lipids extracted from 14 bacterial strains of Azotobacter chroococcum as well as from strains of Pseudomonas aureofaciens, P. chlororapsis, and P. fluorescens. The amount of alkylresorcinols found varied from 2.3 to 56.2 g/mg (dry weight) of cells in A. chroococcum and from 0.2 to 0.8 g/mg (dry weight) of cells in Pseudomonas spp. Strains of both genera produce saturated homologs with C 13 to C 27 side chains. C 19 , C 21 , and C 23 homolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 18 publications
2
15
0
1
Order By: Relevance
“…The AR-containing fraction (4.8 mg) was purified from the cell extract by column chromatography on Sephadex LH-20 followed by preparative TLC, whereas no ARs were detected in the post-culture medium extract. Our finding is in a good agreement with previously published studies of ARs in A. vinelandii (Reusch and Sadoff, 1979;Su et al, 1981), however remains inconsistent with the report by Kozubek et al (1996), who demonstrated the presence of small quantities of ARs also in supernatants. From a physico-chemical point of view, secretion of certain amounts of ARs into the culture liquid medium is possible due to their amphiphilic character and, in fact, has been found in few microorganisms (Zarnowski et al, 2000a;Zarnowski, Hendrich and Pietr, unpublished).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…The AR-containing fraction (4.8 mg) was purified from the cell extract by column chromatography on Sephadex LH-20 followed by preparative TLC, whereas no ARs were detected in the post-culture medium extract. Our finding is in a good agreement with previously published studies of ARs in A. vinelandii (Reusch and Sadoff, 1979;Su et al, 1981), however remains inconsistent with the report by Kozubek et al (1996), who demonstrated the presence of small quantities of ARs also in supernatants. From a physico-chemical point of view, secretion of certain amounts of ARs into the culture liquid medium is possible due to their amphiphilic character and, in fact, has been found in few microorganisms (Zarnowski et al, 2000a;Zarnowski, Hendrich and Pietr, unpublished).…”
Section: Resultssupporting
confidence: 84%
“…Our finding is in a good agreement with previously published studies of ARs in A. vinelandii (Reusch and Sadoff, 1979;Su et al, 1981), however remains inconsistent with the report by Kozubek et al (1996), who demonstrated the presence of small quantities of ARs also in supernatants. From a physico-chemical point of view, secretion of certain amounts of ARs into the culture liquid medium is possible due to their amphiphilic character and, in fact, has been found in few microorganisms (Zarnowski et al, 2000a;Zarnowski, Hendrich and Pietr, unpublished). AR molecules exhibit an affinity to biological membranes, because their partition coefficient in an octanol/water system is more than 7.4 (Kozubek and Tyman, 1999).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Estos metabolitos han sido encontrados en varios organismos de plantas, hongos, bacterias y esponjas marinas (Barrow y Capon, 1991; Kozubek et al, 1996; Kozubek y Tyman, 1999; Zarnowski et al, 1999;Zarnowski et al, 2000a). Los lípidos resorcinólicos estructuralmente están definidos por una molécula con características anfipáticas debido a que en su estructura tiene una cadena alquil hidrofóbica derivada de la biosíntesis de los ácidos grasos y un anillo resorcinol hidrofílico proveniente de la vía biosintética de los policétidos; tal estructura le confiere numerosas propiedades, asociadas a la conformación de la bicapa lipídica, respiración mitocondrial, bioquímica celular, y estructura de la membrana, afectando las propiedades físico-químicas de microorganismos patógenos, (Kozubek y Tyman, 1999;Zarnowski et al, 2002;Bitkov et al, 1992).…”
Section: Introductionunclassified